Perfusion scintigraphy in the assessment of autologous cell therapy in diabetic patients with critical limb ischemia - Nemcova, A; Jirkovska, A; Dubsky, M; Bem, R; Fejfarova, V; Woskova, V; Pysna, A; Buncova, M (Physiological research, 2018)
Perfusion scintigraphy with technetium-99-methoxy-isobutyl-isonitrile ((99m)Tc-MIBI) is often used for assessing myocardial function but the number of studies concerning lower limb perfusion is limited. The aim of our study was to assess whether (99m)Tc-MIBI was an eligible method for evaluation of the effect of cell therapy on critical limb ischemia (CLI) in diabetic patients. (99m)Tc-MIBI of calf muscles was performed before and 3 months after autologous cell therapy (ACT) in 24 diabetic patients with CLI. Scintigraphic parameters such as rest count and exercising count after a stress test were defined. These parameters and their ratios were compared between treated and untreated (control) limbs and with changes in transcutaneous oxygen pressure (TcPO(2)) that served as a reference method. The effect of ACT was confirmed by a significant increase in TcPO(2) values (p<0.001) at 3 months after ACT. We did not observe any significant changes of scintigraphic parameters both at rest and after stress 3 months after ACT, there were no differences between treated and control limbs and no association with TcPO(2) changes. Results of our study showed no significant contribution of (99m)Tc-MIBI of calf muscles to the assessment of ACT in diabetic patients with CLI over a 3-month follow-up period.
Keywords: senioři; buněčná a tkáňová terapie; Diabetic Foot; Male; Perfusion Imaging; Middle Aged; mužské pohlaví; Diabetes Mellitus, Type 2; diabetes mellitus 2. typu; Transplantation, Autologous; ženské pohlaví; perfuzní zobrazování; Humans; technecium 99mTc sestamibi; Technetium Tc 99m Sestamibi; lidé středního věku; autologní transplantace; Leg; Cell- and Tissue-Based Therapy; bérec; Female; Aged; lidé; diabetická noha